Culture and Agriculture In the North American Context - Ervin, Alexander M. (Culture)

(untitled) (Canadian Anthropology Society / Société Canadienne d’Anthropologie (CASCA), formerly/anciennement Canadian Ethnology Society / Société Canadienne d’Ethnologie, 1985)
This paper reviews the anthropological literature relating to culture and modern capital intensive farming in North America. The author argues that there is a legitimate niche for anthropological enquiry in spite of the dominance of Agricultural Economics and Rural Sociology. Domains of enquiry that are advocated include: holistic community studies, studies of cultural and historical developments of agricultural practices, farm unit ethnographies, comparative regional analyses, examination of agrarian values and applied advocacy research.